831 Evaluation of Trends in Gait Function Following Ventriculoperitoneal Shunt Placement in Patients with Idiopathic Versus Secondary Versus Neurodegenerative NPH: A Long Term Follow-Up of 63 Patients. (April 2023) - Cunningham, Coby; Barpujari, Awinita; Kujawski, Brandon; Thompson, Diane; Lonich, Ian; Leonardo, Jody
Abstract : INTRODUCTION: Normal Pressure Hydrocephalus (NPH) most commonly presents in the elderly with symptoms such as gait dysfunction, urinary incontinence, altered mentation. In the current literature three categories of NPH are commonly considered: idiopathic (iNPH), secondary (sNPH), and neurodegenerative (nNPH). Due to variability in the causative pathology, NPH patients in each category may respond differently to ventriculoperitoneal shunt (VPS) placement over the long term. METHODS: An IRB approved retrospective review was conducted on 63 patients with diagnosed iNPH, sNPH, or nNPH who underwent shunt placement (2016 - present). Each patient was closely followed by a single surgeon and specialized team at our adult hydrocephalus clinic from time of symptomatic presentation through diagnosis, shunt placement, and post-operative assessments. Assessment at all pre- and post-operative visits included gait assessment via timed 25' walk test (TW) and timed up-and-go (TUG) test. RESULTS: Long-term outcomes for the TW test, measured from baseline to most recent follow-up show that iNPH patients averaged an improvement of 4.83s (seconds), while sNPH and nNPH patients averaged improvements of 4.25s and 2.98s, respectively. Following the TUG test, the average improvement for iNPH patients was 4.37, with the improvement averages for sNPH and nNPH being 15.33s and 3.09s, respectively. CONCLUSIONS: There is a noticeable difference in the objective gait measurements at post-shunting follow-up among patients diagnosed with the three major categories of NPH. We believe the root of this variability lies within the specific causative factors for the respective patients' NPH and may be particularly affected by the progressive degenerative nature of the nNPH category. Careful categorization of patients into each group may aid surgeons as they council their patients and set expectations for realistic post-operative courses.